When a Child is Speech Delay: Causes, Diagnosis, and Intervention - Choirul Maromi; Pamuji Pamuji (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
Speech Delayin children is a developmental problem that often raises concerns for parents and health professionals. This research aims to identify the causes, diagnostic methods and effective interventions for treating speech delays in children. The causes of speech delays can vary, including genetics, environment, hearing loss, and medical and neurological conditions such as autism and language spectrum disorders. A diagnosis of speech delay requires a comprehensive evaluation by a multidisciplinary team that includes a pediatrician, speech pathologist, psychologist, and audiology specialist. Assessment tools such as language development tests and clinical observations are often used to assess a child's speech and language abilities. Effective interventions include speech therapy, language stimulation programs, as well as active involvement of parents in therapy. In addition, early intervention is highly recommended to maximize a child's speech development potential. This research emphasizes the importance of early detection and appropriate intervention to overcome speech delays and support optimal communication development in children.┬á